Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s00330-023-10256-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics in cone-beam breast CT for the prediction of axillary lymph node metastasis in breast cancer: a multi-center multi-device study

Yueqiang Zhu,
Yue Ma,
Zhenzhen Zhai
et al.

Abstract: ObjectivesTo develop a radiomics model in contrast-enhanced cone-beam breast CT (CE-CBBCT) for preoperative prediction of axillary lymph node (ALN) status and metastatic burden of breast cancer.Methods Two hundred and seventy-four patients who underwent CE-CBBCT examination with two scanners between 2012 and 2021 from two institutions were enrolled. The primary tumor was annotated in each patient image, from which 1781 radiomics features were extracted with PyRadiomics. After feature selection, support vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Although the exact biological characteristics captured by these 2 features cannot be determined, it is hypothesized that these subtle details may be associated with slight changes in microvessel density and the tumor microenvironment. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact biological characteristics captured by these 2 features cannot be determined, it is hypothesized that these subtle details may be associated with slight changes in microvessel density and the tumor microenvironment. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…CE-CBBCT has shown promising results in lesion identification and differentiation, [ 14 , 15 ] molecular subtyping, [ 16 , 17 ] assessment of disease extent, [ 12 , 18 ] and prediction of axillary lymph node metastasis. [ 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis has shown that the diagnostic sensitivity of CBBCT was higher than that of DM and ultrasound, and CE-CBBCT has comparable sensitivity but slightly lower speci city compared to MRI [17,18]. In addition, CBBCT has shown promise in preoperative assessment, including determining the extent of the primary tumor [19,20] and predicting axillary lymph node metastasis [21,22]. Some studies have also suggested that CE-CBBCT features can assist in characterizing IHC receptor status and distinguishing molecular subtypes of breast cancer [13,23,24].…”
Section: Introductionmentioning
confidence: 99%